Integrating Business Courses Mentorship Programs and Investment to Enhance Entrepreneurial Opportunities - Utama, Iston Dwija; Prabowo, Puji; Mohd, Zalena (Pandawan, 2025)
Much research highlights the role of business incubators in fostering student entrepreneurship, but the impact of business courses and mentoring programs on recognizing business opportunities remains underexplored. This study investigates how entrepreneurship education, mentorship, and investment enhance students ability to identify and create business opportunities, particularly in uncertain times. Data were collected from 205 third-year university students with experience in incubator and mentoring programs conducted by universities or external organizations. A quantitative approach was employed, utilizing SMART-PLS tools to analyze correlations between entrepreneurship education, mentorship, investment, and opportunity recognition. Results show investment and mentoring have the strongest correlation, highlighting the importance of financial and non-financial support for entrepreneurial success. The findings emphasize the significance of a well-designed curriculum in fostering business opportunity recognition, with mentoring programs mediating the relationship between educational and financial support. Integrating education, mentorship, and investment significantly influences student ventures by fostering entrepreneurial intentions and providing critical resources. Collaboration among educational institutions, policymakers, and investors is vital to establish comprehensive support systems that prepare future entrepreneurs to succeed in dynamic markets.